Information literacy profile of biology education students in different batch - Dian Tauhidah; Erna Wijayanti (Universitas Negeri Jakarta, 2023)
Information literacy is one of the basic skills that students must have in today's digital era. This research was conducted to analyze the information literacy profile of students in different batch years. This quantitative study compared three groups of data based on the student year. The research population was all biology education students at UIN Walisongo Semarang. The research sample was determined using a stratified random sampling technique to obtain 94 students divided into three grades. The data were obtained using the information literacy test instrument and analyzed using the ANOVA test. Information literacy indicators consist of identifying information, accessing information, evaluating information, using information effectively, and understanding the ethics of using information. The study results show that students in all classes have information literacy skills in the sufficient category, but significant differences exist between batch years. The lowest information literacy ability was in first-year students, followed by second-year students, and the highest in third-year students. The study results indicate the need to increase students’ information literacy.